Shrubs for mitigating pollution and improving health - Janakiram, T; Jain, Ritu; Lakshmipathy, M. (Indian Horticulture, 2019)
The shrubs are considered as an important component in green initiatives to combat pollution and improvement of human health. They should be planted and gardens should be made beautiful.